Mesenteric vasculitis in children with systemic lupus erythematosus. Issue 3 (March 2016) - Fotis, Lampros; Baszis, Kevin; French, Anthony; Cooper, Megan; White, Andrew
Abstract Lupus mesenteric vasculitis (LMV) is a severe and potentially fatal complication of systemic lupus erythematosus (SLE). Although LMV is always a consideration in adolescents and adult patients with SLE, who present with acute abdominal pain, diagnosis and management remain a great challenge. We describe the cases of five patients age 14 to 21 years old diagnosed with LMV. All five patients had active SLE and typical clinical presentation suspicious of LMV. Abdominal CT was the preferred imaging modality and was useful in four patients. Corticosteroids were the mainstay of treatment for all five patients. All five patients survived and complete remission of symptoms was achieved in four out of five patients with the addition of cyclophosphamide and in one out of five with rituximab. A review of the literature was performed including a systemic review of the case reports and case series published in the English literature over the last 20 years.